Photocatalytic degradation of methylene blue dye utilizing nano-TiO2 with montmorillonite: Characterization, process and kinetic studies - Ng Wen Jia (School of Bioprocess Engineering, University Malaysia Perlis, 2011)
Nano-titanium dioxide (nano-TiO2) photocatalyst was synthesized through sol-gel method. A sol-gel solution was prepared using the formulation of 1 TTIP: 2 C2H5OH: 5. H20. A simple batch reactor was designed and used for process studies. The photocatalytic degradation of methylene blue was studied under different operating parameters. The initial methylene blue concentration, catalyst dosage and pH value of methylene blue were studied as important process variables. The nano-TiO2 catalyst was characterized by using Scanning Electron Microscopy (SEM) and Energy Dispersive X-ray Spectroscopy (EDX) analysis. The degradation of Methylene Blue (MB) concentration under UV radiation is more efficient compared to without ultraviolet (UV) radiation. The highest percentage of degradation was achieved when the concentration of methylene blue was at 20ppm. The degradation of MB increased with an increase in catalyst dosing up to an optimum loading of 0.75g. Degradation efficiency decreased in the order of pH2 > pH5 > pH7 > pH9. The photocatalytic degradation of methylene blue shows a pseudo-first order kinetics. The highest apparent rate constant, kapp was achieved at the initial concentration of 20ppm, which is 0.0183min-1. The kinetics evaluation on methylene blue degradation was also studied to determine the rate constant, k and adsorption equilibrium constant, K. The value of k and K were estimated by using non-linear regression in POLYMATH software.